Bioinspired Synthesis of ZnO@polydopamine/Au for Label-Free Photoelectrochemical Immunoassay of Amyloid-β Protein - He, Guangli; Zhou, Yue; Li, Mifang; Guo, Yanzhen; Yin, Hang; Yang, Baocheng; Zhang, Shouren; Liu, Yibiao (Frontiers in Bioengineering and Biotechnology, 2021)
Amyloid-β protein (Aβ) is an important biomarker and plays a key role in the early stage of Alzheimer’s disease (AD). Here, an ultrasensitive photoelectrochemical (PEC) sensor based on ZnO@polydopamine/Au nanocomposites was constructed for quantitative detection of Aβ. In this sensing system, the ZnO nanorod array decorated with PDA films and gold nanoparticles (Au NPs) have excellent visible-light activity. The PDA film was used as a sensitizer for charge separation, and it also was used for antibody binding. Moreover, Au NPs were loaded on the surface of PDA film by in situ deposition, which further improved the charge transfer efficiency and the PEC activity in visible light due to the localized surface plasmon resonance effect of Au NPs. Therefore, in ZnO@polydopamine/Au nanocomposites, a significantly enhanced photocurrent response was obtained on this photoelectrode, which provides a good and reliable signal for early detection of AD. Under the optimized conditions, the PEC immunosensor displayed a wide linear range from 1 pg/mL to 100 ng/mL and a low detection limit of 0.26 pg/mL. In addition, this PEC immunosensor also presented good selectivity, stability, and reproducibility. This work may provide a promising point-of-care testing method toward advanced PEC immunoassays for AD biomarkers.